Analisis Unsur-Unsur Pidana Pemalsuan Pasal 263 Ayat (1) KUHP JO Pasal 55 Ayat (1) Ke-1 KUHP dalam Surat Keterangan Bebas Covid-19 - Abdul Hayy Nasution (Neolectura, 2022)
The extraordinary circumstances of the Covid 19 disaster in 2019 the Indonesian government won swiftly by issuing a number of regulations for handling Covid 19 in the country. This study aims to analyze criminal acts in the Forgery of Covid 19-free rancidity letters, but to prove it as a criminal act, objective elements and subjective elements must be fulfilled as a mistake as well as the criminal act has fulfilled the nature of being against the law as the charges so that it can be subject to punishment because it has been proven to be legally against the law and against the material law. The research method used is qualitative with documentation data collection techniques that refer to certain regulations in drawing conclusions. Hasal this research is a criminal act as an act threatened by the law because it is contrary to the law it is done by someone who is able to be responsible, there are two groups of elements to criminal acts such as objective elements and subjective elements, something from outside the perpetrator in the form of actions that are prohibited / required, consequences, and certain circumstances are temporary objective elements attached to the perpetrator in the form of errors and abilities responsible is a subjective element.